OPTIMASI DIGESTI ENZIM RESTRIKSI SacII PADA ISOLAT Mycobacterium tuberculosis H37Rv UNTUK DETEKSI MUTASI PROMOTER inhA PADA KASUS MDR-TB DENGAN METODE PCR-RFLP - Putri, Ida Ayu Ratih Dwi Nugraha; Yowani, Sagung Chandra; Wirajana, I Nengah (Metamorfosa: Journal of Biological Sciences, 2017)
The aim of this study was to optimize the digestion process of SacII restriction enzyme in Mycobacterium tuberculosis H37Rv isolate. SacII enzyme that have CCGC^GG restriction site could be used to detect the mutation at -24 promoter region of inhA M. tuberculosis . The mutation in this position is one of the causes of isoniazid resistance. The methods of this study were conducted in several step, respectively: DNA isolation of M. tuberculosis H37Rv, amplification of inhA promoter region of M. tuberculosis H37Rv using PCR method, and digest optimization using SacII. In this study, optimization of SacII digestion was conducted for formulaion and incubation time. The formulation was optimized by GM-ONE Buffer and GM-Buffer IV, meanwhile the incubation time was optimized in 1 hour, 2 hour, and 3 hour. The result of this study showed that SacII work optimally in GM-Buffer IV compared to GM-ONE Buffer and incubate for 3 hours. Under the optimal digest condition, SacII enzyme could be used to detect the mutation at -24 promoter region of inhA in the case of MDR-TB using PCR-RFLP method.
Keywords: Digest optimization, PCR-RFLP, Restriction enzyme, SacII, M. tuberculosis, inhA Promoter